Digitalisasi Ekonomi Syariah di Kalangan Generasi Z Untuk Peningkatan Literasi Keuangan Syariah (Studi Kasus Mbanking BSI) - Umu Nusaibah (Universitas Muhammadiyah Ponorogo, 2023)
Generation Z is a generation that is active in using the internet, and is also active in communicating through cyberspace, such as using social media applications or messaging applications, with these characteristics, generation Z will become a generation that plays an important role in the development of the Indonesian state. Generation Z is synonymous with digital technology, and also relies heavily on digital communication tools in everyday life. So that digital technology is no longer just a contemporary style but has become a necessity for various activities. This research was conducted to determine the extent of the potential of Generation Z in the development of Islamic economics. The research method uses a literative qualitative method which explains the behavior of Indonesia's Z generation in digital technology or mobile banking and the potential that can be utilized for economic development. The analysis technique used in this case is by reviewing various literature, presenting good data through the observations of generation Z phenomena researchers, then proceed with drawing conclusions.